2020
DOI: 10.3390/jof6030149
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi Isolated from Plants Growing in Central Andean Precordillera of Chile with Antifungal Activity against Botrytis cinerea

Abstract: Botrytis cinerea is an important phytopathogenic fungus affecting the fruit production around the world. This fungus is controlled mainly by using synthetic fungicides, but many resistant isolates have been selected by the indiscriminate use of fungicides. Endophytic fungi or secondary metabolites obtained from them become an alternative method of control for this fungus. The aim of this work was to identify endophytic fungi with antifungal activity against the plant pathogenic fungus B. cinerea isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The genera Colletotrichum and Diaporthe are important causative agents of anthracnose to many crops and a grapevine dieback disease, respectively [ 73 , 74 ]. Increasing evidence showed that fungal endophytes recovered from native or endemic plants may hold significant interest for their bioactive compound production and were shown to be useful in attacking pathogens [ 21 , 26 , 28 , 75 ]. For instance, three fungal endophytes from endemic plants in Central Andean Precordillera were found to secrete volatile compounds and suppressed the sporulation of filamentous necrotrophic fungus Botrytis cinerea [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genera Colletotrichum and Diaporthe are important causative agents of anthracnose to many crops and a grapevine dieback disease, respectively [ 73 , 74 ]. Increasing evidence showed that fungal endophytes recovered from native or endemic plants may hold significant interest for their bioactive compound production and were shown to be useful in attacking pathogens [ 21 , 26 , 28 , 75 ]. For instance, three fungal endophytes from endemic plants in Central Andean Precordillera were found to secrete volatile compounds and suppressed the sporulation of filamentous necrotrophic fungus Botrytis cinerea [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence showed that fungal endophytes recovered from native or endemic plants may hold significant interest for their bioactive compound production and were shown to be useful in attacking pathogens [ 21 , 26 , 28 , 75 ]. For instance, three fungal endophytes from endemic plants in Central Andean Precordillera were found to secrete volatile compounds and suppressed the sporulation of filamentous necrotrophic fungus Botrytis cinerea [ 75 ]. Likewise, fungal isolates recovered from native Chilean gymnosperms also showed positive inhibition activity against several pathogens [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are microorganisms that can live inside tissue of living plants without showing any disease symptoms [8]. Endophytes can produce different secondary metabolites with biological activities such as antibacterial, fungicidal, and algicidal properties [9][10][11]. Different compounds from endophytes possessing antifungal activity against B. cinerea have been described so far, including monoterpene derivatives obtained from the plant endophytic fungus Pestalotiopsis foedan [12], hydroxyanthraquinone derivatives from Coniothyrium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Eight gymnosperm species of southern of Chile, Araucaria araucana, Austrocedrus chilensis, Fitzroya cupressoides, Pilgerodendron uviferum, Podocarpus nubigena, Podocarpus saligna, Prumnopitys andina, and Saxegothaea conspicua were analyzed and thirty-eight endophytic fungi, some of these producing antifungal compounds, were isolated [17]. Also, it has been described that foliar endophytic fungi isolated from the Chilean tree Embothrium coccineum present low antifungal activity against B. cinerea [18] and, more recently, endophytic fungi from the endemic plant Echinopsis chiloensis with antifungal activity against B. cinerea have been described by Vidal et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a set of microbial endophytes with multiple plant-growth promoting traits can positively in uence the life cycle and physiological responses of young U. europaeus plants.Similarly, our results agree withHormazabal and Piontelli (2009), who showed that crude extracts from endophytic fungal strains (including the genus Acremonium) have biocontrol activity against phytopathogenic fungal strains. Similarly,Vidal et al (2020) also isolated and characterized endophytic fungi associated with the native plant Acacia caven and tested against B. cinerea. Regarding bacteria, strong biocontrol potential was detected in the isolate Rhodococcus sp., which agrees with…”
mentioning
confidence: 99%